IDENTIFIKASI BAKTERI YANG TUMBUH PADA OLAHAN ABON IKAN CAKALANG (Katsuwonus pelamis L.) DARI UMKM KOTA BITUNG - Daud, Putri; Naharia, Orbanus; Lawalata, Helen Joan; Setyawati, Iriani; Nangoy, Wiesye M. S> (SOSCIED, 2024)
Skipjack Tuna (Katsuwonus pelamis L.) is a pelagic fish that dominates the waters of the Indian and Pacific Oceans. This fish has unique physical characteristics, including an aerodynamic body, a metallic blue or teal back, and transverse stripes that distinguish it from other species. In Indonesia, skipjack tuna is abundant in the waters of Manado and Maluku. This study aims to determine the types of bacteria present in processed skipjack tuna floss (abon cakalang) based on morphological and physiological characteristics through biochemical tests. This study employs a qualitative descriptive approach conducted in a laboratory setting. Data were gathered through direct observation of samples undergoing various tests and subsequently presented in a descriptive manner. Based on the identification data, 30 bacterial isolates were found in the processed skipjack tuna floss. The isolates were identified macroscopically and microscopically. The findings of the study reveal that the bacteria found in processed skipjack tuna floss, based on biochemical tests and profile matching, are suspected to belong to the Staphylococcus and Vibrio genera.